Value added by the doctorate of social work: professional satisfaction, scholarly leadership, and practice-informed research. Issue 8 (17th November 2022) - Bradley, Samuel Lewis; Gold, Sheila Korones; Hansel, Tonya Cross
ABSTRACT: As social work doctoral programs are undergoing a substantive shift, in the United States, more institutions of higher education are trending towards a resurgence of a doctorate of social work degree (DSW). However, little attention has been given to the experiences of DSW students. The purpose of this cross-sectional study is to explore why students choose DSW education, professional aspirations, and intended contributions to the field of social work. Findings suggest that 85% of participants noted flexibility as a key selling point and that perceived value added includes professional satisfaction, scholarly leadership, and practice-informed research. The DSW offers the added value of producing seasoned clinical professionals who become highly trained in theory, policy, and research.